Preparation of Zirconium Carbide-Zirconium Silicide Composite Powders by Solid Reaction of Zr and SiC Powders - Yingxin CHEN (Medžiagotyra, 2020)
In the present work, zirconium carbide-zirconium silicide composite powders were prepared by solid reaction using Zr and SiC powders as reactants. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) results showed that, after treatment at 800 ºC, the produced zirconium carbide-zirconium silicide diffusion layer was very thin and mainly consisted of ZrC and ZrSi2. After treatment above 900 ºC, the produced phases were mainly consisted of ZrC and ZrSi2, plus less ZrSi.